2021
DOI: 10.1183/16000617.0096-2021
|View full text |Cite
|
Sign up to set email alerts
|

Recycling plastic: diagnosis and management of plastic bronchitis among adults

Abstract: Plastic bronchitis is a rare, underdiagnosed and potentially fatal condition. It is characterised by the formation and expectoration of branching gelatinous plugs that assume the shape of the airways. These airway plugs differ from the allergic mucin that characterises allergic bronchopulmonary aspergillosis and mucoid impaction of the bronchi. Plastic bronchitis is most often encountered in the paediatric population following corrective cardiac surgery, such as the Fontan procedure. It also occurs in adults. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 63 publications
(86 reference statements)
0
9
0
1
Order By: Relevance
“…When children with no known history of foreign bodies present with comorbid long-term pulmonary infection, it is important to be vigilant against endogenous foreign bodies. Previous reports have suggested that almost all plastic bronchitis is accompanied by atelectasis or pulmonary consolidation [ 31 , 32 ]. In this study, the cases of obstructive emphysema and atelectasis were spontaneously relieved after the foreign bodies were removed.…”
Section: Discussionmentioning
confidence: 99%
“…When children with no known history of foreign bodies present with comorbid long-term pulmonary infection, it is important to be vigilant against endogenous foreign bodies. Previous reports have suggested that almost all plastic bronchitis is accompanied by atelectasis or pulmonary consolidation [ 31 , 32 ]. In this study, the cases of obstructive emphysema and atelectasis were spontaneously relieved after the foreign bodies were removed.…”
Section: Discussionmentioning
confidence: 99%
“…Consistency, cohesiveness, formation of bronchial casts differentiate this entity from other mucus pluggings. [41]. Usually seen in the paediatric population who underwent cardiac surgeries like Fontan's operation.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrin, mucin along with lymphocytes and macrophages as seen in lymphatic abnormalities 3. Mucin /degenerated eosinophils as in ABPA [41].…”
Section: Normal Mucus Densitymentioning
confidence: 99%
See 2 more Smart Citations